425 The Impact Of COVID-19 On Hernia Surgery in The Lothian Region Of Scotland. (12th October 2021) - Ewing, A; Hodge, K; McFadyen, R; Grossart, C; East, B; de Beaux, A
Abstract: Aim: The COVID-19 pandemic resulted in a lockdown in South East Scotland on the 23 March 2020. This had an impact on the volume of benign elective surgery able to be undertaken. The degree to which this reduced hernia surgery was unknown. The aim of this study was to review the hernia surgery workload in the Lothian region of Scotland and assess the impact of COVID-19 on hernia surgery. Method: The Lothian Surgical Audit database was used to identify all elective and emergency hernia operations over a six-month period from 23 March 2020, and for the same time period in 2019. Data was collected on age, gender, location of the hernia, type of hernia repair and whether elective or emergency operation. Results: The number of hernia repairs reduced dramatically between 2019 and 2020 (570 versus 149). The majority of this can be explained by a reduction in elective operating (488 versus 87). There was, however, also a reduction in the numbers of hernias repaired as an emergency over the same study periods (82 to 62). Lockdown in 2020 had the biggest effect on elective incisional hernia repair (74 versus 2). Conclusions: The COVID-19 pandemic has reduced both the number of elective and emergency hernia operations in 2020 compared to 2019. While the reduction in elective surgery has not resulted in an associated increase in emergency surgery over the study period, it is possible that if continuing reduced availability to elective hernia surgery continues in Lothian, the emergency hernia workload may increase.